برامج الماجستير الأجنبية عن بعد المعتمدة في المکتبات والمعلومات: دراسة وصفية - نورة محمدي الشنوانى (المجلة الدولية لعلوم المكتبات والمعلومات)
Many librarians and professionals as well as graduates need to obtain a master’s degree as a first step in preparation for the completion of the graduate studies process to develop scientific and practical skills as well as career advancement. Offering fully remote master’s programs is an appropriate method for specializing in libraries and information from the point of view of students as well as those in charge of library schools, and in light of In this huge number of universities that offer these programs, there may be programs that are not academically accredited.Therefore, the most important remotely accredited master’s programs will be identified in terms of the objective of the master’s program and accreditation organizations. Monitoring the admission requirements. Presenting the teaching methods used and monitoring the target group of the master’s program. Curriculum, professional recognition organizations, job opportunities and training provided by obtaining an internationally accredited master’s degree The study reached a number of results, including the diversity of the organizations accrediting the master’s programs approved by the study